Employer Survey Snapshot 2016 : Highlights from Six Low and Middle-Income Countries - Sanchez Puerta, Maria Laura; Valerio, Alexandria; Hoftijzer, Margo; Rizvi, Anam; Avato, Johanna (World Bank, Washington, DC, 2016)
The Employer Survey Snapshot features a descriptive analysis of the data collected during the first two waves of the Skills Towards Employment and Productivity (STEP) Employer Surveys. Key objectives of the Snapshot are (1) to explain the motivation and relevance behind the implementation of employer skills surveys and (2) to highlight some of the observed cross-country patterns from six participating countries, namely, Armenia, Azerbaijan, Georgia, Sri Lanka, Vietnam and China (Yunnan Province). The Snapshot provides information on how employers view jobs mismatch and how they identify and value worker skills sets. In addition, it includes insights from innovative firms and examples of training provisions. A section on survey methodology has also been included as an annex.